Energy Vulnerability and the Social Bonus (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
Starting from the perspective of vulnerable customer protection in the European Union in order to frame the measures taken in Spain, the paper analyzes the social bonus experience and the problems that the recent regulatory changes adopted by the legislator pose.
Keywords: vulnerable customers; social bonus; poverty; electricity